Sleep monitoring by millimeter wave radar sensor - Ma, Yuchen (Nanyang Technological University, 2022)
Sleep monitoring system becomes popular in recent years. Heartbeat and respiration are two essential vital sign signals to expose general health conditions during sleep. This project trends a piece of news that happened this year, in China. A senior woman who is leaving alone suffered from a sudden stroke and could not make any movements. The elderly were rescued after two days, in the same position after falling, after the neighbor scented out the noise. Nowadays, elderlies who are living alone may face the potential risk of sudden heart attack, without any surveillance from their children or doctors. Currently, there are wearable devices that have sleep monitoring functions, but they may cause skin problems such as allergies on sensitive skin. In this project, we proposed to design a contactless sleep monitoring system using radar technologies and data processing methods. The sleep monitoring system managed to perform a wireless detection of vital signs, such as heart rate and respiration rate, during sleep. Millimeter rave radar was used to monitor the chest motion, Fourier transform-based methods were applied for frequency resolutions, and band-pass filters were exercised to separate multiple vital sign signals. Besides radar signal processing, we designed a test app for displaying real-time heart rate. In this app, we increased the testing efficiency, by adding buttons to execute, monitor, and plot the data. It will provide a user-friendly sleep heart rate monitoring system, with simpler steps and a more straightforward display.